2020
DOI: 10.1021/acs.jmedchem.0c00475
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Identification of a Novel Lead Targeting Survivin Dimerization for Proteasome-Dependent Degradation

Abstract: Survivin, a homodimeric member of the Inhibitor of Apoptosis Protein (IAP) family, is required for cancer cell survival and overexpressed in almost all solid tumors. However, targeting survivin has been challenging due to its "undruggable" nature. Recently, we used a novel approach to target the dimerization interface and identified inhibitors of two scaffolds that can directly bind to and inhibit survivin dimerization. One of the scaffolds, represented by the compound LQZ-7, contain an undesirable labile hydr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
24
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(28 citation statements)
references
References 21 publications
0
24
0
Order By: Relevance
“…Degradation of the dimeric proteins can result from the interaction with the hydrophobic dimerization interface, which leads to conformational changes. This degradation can be mediated by the proteasome enzyme [ 12 ]. Since 5c and 5e were expected to inhibit survivin dimerization as shown in the docking study, we assumed that they may induce the degradation of survivin via the proteasome.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Degradation of the dimeric proteins can result from the interaction with the hydrophobic dimerization interface, which leads to conformational changes. This degradation can be mediated by the proteasome enzyme [ 12 ]. Since 5c and 5e were expected to inhibit survivin dimerization as shown in the docking study, we assumed that they may induce the degradation of survivin via the proteasome.…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, it is considered as a cancer-specific biomarker. Hence, targeting survivin embodies an attractive strategy for the development of more selective anticancer therapeutics [ 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…Once the tumor reached 200 cm 3 , the mice were randomly divided into two groups (n = 5 per group). According to previous studies 20 , 21 , compound 3K (5 mg/kg body weight) dissolved in 1 ml of solvent (DMSO:corn oil, 1:9) was administered orally every 2 days for 31 days. The control group was treated with an equal volume of the vehicle.…”
Section: Methodsmentioning
confidence: 99%
“…As a central player in cell biology and a therapeutic target, STAT3 is a transcription factor that regulates cell differentiation, proliferation and apoptosis, resulting in promoting cancer progression (88). Chen et al (89) reported that ropivacaine (0.25, 0.5 and 1 mM) possessed inhibitory effects to cervical cancer SiHa, Caski cells via suppressing the expression of cyclin D1 and survivin, an anti-apoptotic protein (90,91), by abrogating the phosphorylation and transcriptional activation of STAT3 whose overexpression could reverse the cytotoxicity of ropivacaine (89). These effects were mediated by up-regulating MEG2 and down-regulating microRNA96, suggesting ropivacaine as a potential therapeutic agent for cervical cancer (89).…”
Section: Via Micro Rnas/long Non-coding Rnas (Lncrnas) and Associated...mentioning
confidence: 99%